2018
DOI: 10.26912/sdj.v2i1.1913
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of yogurt containing probiotic Bifidobacterium lactis reduces Streptococcus mutans in orthodontic patients

Abstract: Background: Probiotic bacteria is commonly used as a food supplement intended to benefit the host by improving intestinal bacterial balance. Probiotics have also been investigated from the perspective of oral health. Objectives: The purpose of this study was to investigate the effect of daily intake of yogurt containing probiotic Bifidobacterium animalis subsp. lactis BB-12 (B. lactis) on salivary Streptococcus mutans (S. mutans) counts in patients undergoing fixed orthodontic treatment. Methods: Saliva sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A recent study showed that probiotic yogurt containing Bifidobacterium lactis BB-12 consumption can reduce the levels of S. mutans as pathogenic bacteria in the saliva. [ 8 ] Among these bacteria, probiotics are widely used. [ 1 ] Lactobacillus reuteri , as a probiotic bacterium, also has been proven to enhance oral health.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that probiotic yogurt containing Bifidobacterium lactis BB-12 consumption can reduce the levels of S. mutans as pathogenic bacteria in the saliva. [ 8 ] Among these bacteria, probiotics are widely used. [ 1 ] Lactobacillus reuteri , as a probiotic bacterium, also has been proven to enhance oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic supplements and a prebiotic diet are encouraged for children who are deprived of natural breastfeeding to restore their oral microbiome and ensure good oral and dental health [ 50 , 51 ]. To reverse the undesired changes in the microbiota’s composition and function brought on by antibiotic treatments or caesarean delivery, a probiotic mixture in addition to at least partial breastfeeding is highly recommended [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This yogurt consumption could be used to reduce the prevalence of enamel demineralization among patients with fixed orthodontic appliances. 33,34 Probiotics can also enhance oral health through immune system modulation. L. reuteri significantly reduced the production of the pro-inflammatory cytokine, interleukin (IL)-8, and induced the production of human beta defensin-2 in epithelial cells induced by infection with S. mutans and P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%